2009
DOI: 10.1016/j.jebo.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A simultaneous approach to the estimation of risk aversion and the subjective time discount rate

Abstract: In this paper we analyze a sample of 1,832 individuals who responded to six randomly generated lottery questions that differ with respect to chance, prize and the timing of the draw. Using a model that explicitly allows for consumption smoothing, we obtain an estimate of relative risk aversion of 82. Instead, assuming consumption to be immediate gives an estimate of 2, close to what is traditionally reported, while a model of full asset integration gives estimates higher by several orders of magnitude. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 74 publications
2
14
1
1
Order By: Relevance
“…Women, on the other hand, prefer to adopt the product only once it has proved itself in the market. These findings are further supported by Booij and van Praag (2009), who found that the greatest determinants of the adoption of what are normally considered risky purchases are risk and time factors. The greater the perceived risk, the more risk-averse women would be in adopting the product.…”
Section: Gender Differences In Risk-aversionsupporting
confidence: 53%
“…Women, on the other hand, prefer to adopt the product only once it has proved itself in the market. These findings are further supported by Booij and van Praag (2009), who found that the greatest determinants of the adoption of what are normally considered risky purchases are risk and time factors. The greater the perceived risk, the more risk-averse women would be in adopting the product.…”
Section: Gender Differences In Risk-aversionsupporting
confidence: 53%
“…Table 3 shows that, on average, subjects invested 43.4% of their endowment in treatment High and 52.1% in treatment Low-a 8.7 percentage point di¤erence. 12 A Mann-Whitney U test con…rms that the distributions of percentages invested di¤er signi…cantly across treatments (p < 0:0001). This …nding is in line with the treatment e¤ect found in many studies that have used the Gneezy and Potters (1997) design.…”
Section: A …Rst Look At the Datamentioning
confidence: 94%
“…More recent work has focused on the importance of simultaneously estimating the discount rate and the degree of risk aversion (see, for example, Andersen et al 2008;Booij and Van Praag 2009;Duquette et al 2014). Both the degree of risk aversion and the discount rate are parameters in the utility function.…”
Section: Literature Reviewmentioning
confidence: 99%